PENGARUH PENYULUHAN KESEHATAN GIGI DAN MULUT TERHADAP KEBERSIHAN GIGI DAN MULUT - Sukatmi, Sukatmi; Kurniasari, Alfiah (Jurnal AKP, 2013)
Dental and oral hygiene is very big influence to prevent the occurrence of oral and dental problems. Lack of dental and oral hygiene allows the accumulation of plaque and food residue. The purpose of this study to determine the effect of dental and oral health education on the SDN pseudo-V Class IV District Puncu Kediri regency in 2011. The design of this study is the Pre Experiments with One Group Pre - Post Test Design. Entire population students grades 4 SDN Bogus V were 35 students with a sample of 32 students drawn by simple random sampling technique. Data collected by observation and oral dental hygiene criteria debris index and calculus index with analysis of Wilcoxon sign rank test. From the result showed no effect of extension of the debris index (P value: 0.000 <0.05), no effect of extension of the calculus index (P value: 0.655> 0.05) and no effect of education on oral hygiene (p value : 0.000 <0.05). This is due to the extension and assisted with props then there is an increase in knowledge and changes the behavior of dental and oral hygiene. Inferred extension and props can change the behavior so improve dental and oral hygiene. It is recommended that health workers continue to perform outreach using the aids that will greatly assist in conducting outreach to the message - the message of health can both be delivered more clearly, and the target communities can receive the message clearly and precisely as well. With the props people can better understand the health facts that are considered complicated, so they can appreciate how valuable it is health for life. Key words: counseling, teaching aids, dental and oral health